A Henry's law method for generating bulk nanobubbles. Issue 29 (22nd July 2020) - Ferraro, Gianluca; Jadhav, Ananda J.; Barigou, Mostafa
Abstract : A new technique for generating bulk nanobubble suspensions has been developed based on Henry's law which states that the amount of dissolved gas in a liquid is proportional to its partial pressure above the liquid. Abstract : A new technique for generating bulk nanobubble suspensions has been developed based on Henry's law which states that the amount of dissolved gas in a liquid is proportional to its partial pressure above the liquid. This principle which forms the basis of vacuum degasification has been exploited here to produce stable bulk nanobubbles in excess of 10 9 bubble mL −1 in pure water, through successive expansion/compression strokes inside a sealed syringe. We provide evidence that the observed nano-entities must be gas-filled nanobubbles by showing that: (i) they cannot be attributed to organic or inorganic impurities; (ii) they disappear gradually over time whilst their mean size remains unchanged; (iii) their number density depends on the concentration of dissolved gas in water and its solubility; and (iv) added sparging of gas enhances process yield. We study the properties of these nanobubbles including the effects of type of dissolved gas, water pH and the presence of different valence salts on their number density and stability. Given the potential of the technique for large scale production of nanobubble suspensions, we describe a successfully tested automated model and outline the basis for process scale-up.